Stereotyp płci w debacie o prawach kobiet - Helios, Joanna (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The purpose of this article is to present the basic gender stereotypes and their impact on the development of women’s rights. In this study we present two issues: First, the social situation of women in different historical periods – from ancient times through disputes about feminism and gender; secondly, gendered stigma – an overview of basic gender stereotype
Keywords: stereotyp; feminizm; prawa kobiet; równouprawnienie; płeć